Medium- to long-term outcomes after reverse total shoulder arthroplasty with a standard long stem - Bülhoff, Matthias; Zeifang, Felix; Welters, Caroline Charlotte; Renkawitz, Tobias; Schiltenwolf, Marcus; Nolte, Anna-Katharina (Journal of Clinical Medicine, 2022)
Background: Long-term clinical and radiographic outcome data after standard cemented long-stem reverse shoulder arthroplasty (RSA) remain underreported. The aim of this study is to report on medium- to long-term data of patients over 60 years of age. Methods: The same type of RSA (Aequalis Reverse II, Memphis, TN, USA) was implanted in 27 patients with a mean age of 73 years (range 61-84). Indications for RSA were cuff tear arthropathy (CTA) in 25 cases and osteoarthritis (OA) in two cases. Pre- and postoperative Constant Score was assessed and component loosening, polyethylene wear, scapular notching and revision rates were recorded at a mean clinical follow-up (FU) of 127.6 months (SD ± 33.7; range 83-185). Results: The mean-adjusted CS (aCS) improved from 30.0 (range 10-59) to 95.0 (range 33-141) points (p < 0.001). Glenoid loosening was found in two (9.1%) and stem loosening was found in three (13.6%) cases. Polyethylene wear was observed in four (18.2%) cases. Scapular notching appeared in 15 (68.2%) cases but was not associated with poor aCS (p = 0.423), high levels of pain (p = 0.798) or external rotation (p = 0.229). Revision surgery was necessary in three (11.1%) cases. Conclusions: RSA with a cemented standard long stem leads to improvement in forward elevation, abduction and pain after a mean FU of 10 years. However, external rotation does not improve with this prosthetic design. Moreover, scapular notching is observed in the majority of cases, and revision rates (11.1%) as well as humeral loosening rates (13.6%) remain a concern. Level of evidence: Level 4, retrospective cohort study.